Determining the species assemblage and habitat use of cetaceans in the Svalbard Archipelago, based on observations from 2002 to 2014 - Storrie, Luke; Lydersen, Christian; Andersen, Magnus; Wynn, Russell B.; Kovacs, Kit M. (Polar research, 2018)
This study used 13 years of cetacean sighting data (2002-2014) from waters around the Svalbard Archipelago to determine key habitats for year-round resident species as well as seasonally resident species, and to explore spatial overlap between these groups via a combination of kernel density estimation and Maxent modelling. The data set consists of observations made by research vessels conducting various marine studies, coast guard ships and marine-cruise tourist operators. Data are reported from the seasonal period in which there is daylight (March-November), though 95% of the observations occurred June-September. Changes over the study period were investigated, within the limits of the data, to explore whether range shifts may be occurring. Fifteen cetacean species were reported. Among the resident ice-associated cetaceans, only white whales were reported frequently; they were seen exclusively in coastal habitats, in accordance with their known use of tidal glacier fronts for feeding in this region. Narwhal and bowhead whales were rare. Seasonally resident minke whales, fin whales, humpback whales, blue whales and sperm whales as well as small dolphins were seen frequently, in broad and somewhat overlapping habitats. Other less common seasonal residents included killer whales, northern bottlenose whales and sei whales; harbour porpoises and long-finned pilot whales were also reported, but rarely. Shifts over the study period towards higher latitudes, and into coastal environments, were observed for several seasonally resident species. These expansions are likely linked to warming ocean temperatures and a precipitous decline in sea-ice cover in the area.